Building pathways out of poverty for ultra-poor IDPs and vulnerable host communities in Baidoa: Evidence from the endline survey - Leight, Jessica; Hirvonen, Kalle; Karachiwalla, Naureen; Rakshit, Deboleena; Magan, Mohamed (International Food Policy Research Institute, 2025)
The objective of this evaluation is to rigorously assess the effectiveness of the Ultra-poor Graduation Program as implemented by World Vision and ACTED in Baidoa, Somalia